C++ high performance : boost and optimize the performance of your C++ 17 code - Sehr, Viktor (Packt Publishing, 2018)
C++ is a highly portable language and can be used to write both large-scale applications and performance-critical code. It has evolved over the last few years to become a modern and expressive language. This book will guide you through optimizing the performance of your C++ apps by allowing them to run faster and consume fewer resources on the ...